A Pathological Complete Response to the Combination of Ipilimumab and Nivolumab in a Patient with Metastatic Renal Cell Carcinoma - Hana Studentova; Anezka Zemankova; Martina Spisarova; Daniela Skanderova; Zbynek Tudos; Bohuslav Melichar; Vladimir Student (Medicina, 2022)
Background and Objectives: Complete pathological response after ipilimumab and nivolumab combination therapy in a patient with intermediate prognosis renal cell carcinoma is an uncommon finding. Case presentation: A 60-year-old man presented with synchronous solitary metastatic bone lesion and renal cell carcinoma and achieved a complete pathological response after surgical resection of the bone lesion, followed by ipilimumab and nivolumab combination therapy and nephrectomy. The treatment was complicated by hypophysitis and oligoarthritis more than a year after the initiation of the therapy. Conclusions: Currently, the combination therapy based on immune checkpoint inhibitors represents the treatment of choice in patients with intermediate- and poor-risk prognosis metastatic renal cell carcinoma. In the present case, preoperative therapy with ipilimumab and nivolumab resulted in a complete pathological response in the renal tumor. Vigilance concerning potential immune-related side effects is warranted throughout the course of therapy and the subsequent follow-up.